ANALISIS TOTAL LOSS REDAMAN PADA JARINGAN KOMUNIKASI FIBER TO THE HOME (FTTH) MENGGUNAKAN TOPOLOGY BUS DI PERUMAHAN MYRRA RESIDENCE - Cahyanti, Ika Dwi; Pramono, Sholeh Hadi; Prijono, Wahju Adi (Jurnal Mahasiswa TEUB, 2023)
This research analyzes the total attenuation loss in Fiber to the Home (FTTH) networks with the aim of improving signal quality and network efficiency. The study results indicate that the attenuation values at ODP 122 and ODP 123 pose challenges related to total attenuation loss. The standardization of attenuation is 28dB, while the calculated result shows 19.021dB at ODP 122. The Fiber Optic's output power is 3 dBm with a standard input power of -28dBm. The received power at ODP 122 and ODP 123 is -16.021 dB and -15.972 dB, respectively. Although the error values are acceptable, the study suggests improvements in network design, appropriate component selection, and attenuation management strategies to optimize signal quality. Factors such as cable length, cable type, and connectivity also significantly influence network performance. Keywords: Fiber to The Home, Fiber Optic, Loss